EFL TEACHERS’ ASSESSMENT LITERACY - Isnawati, Ida (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
Due to the importance of assessing students’ learning, teachers have to allocate specific time for assessment during the teaching-learning process. For the sake of implementing effective assessment, adequate knowledge and skills of teachers in assessment are badly needed. However, there is an important question related to teachers’ knowledge and skills in assessment, “Do EFL teachers have a good understanding of effective assessment for their students?” This study tried to answer such curiosity by conducting a survey assessment literacy of EFL teachers. The EFL teachers involved in this study were English teachers at several secondary schools in an Indonesian context and the information on their assessment literacy was obtained through a set of Assessment Literacy Inventory (ALI). It was found from this study that the EFL teachers’ assessment literacy was relatively low, indicating their limited knowledge and skills in assessment. Consequently, more continuous and ongoing training, workshop and other teacher professional development are essential to improve the EFL teachers’ assessment literacy.